Editorial Introduction - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2016)
Action research begins with a question about practice, and this volume of Networks presents a variety of questions teacher educators asked about their work with teacher candidates and graduate students. Several of the studies also highlight the cycles of inquiry that can change practice over time.